Adsorption of cobalt by activated carbon from the rice hulls - Teker, M; Saltabas, O; Imamoglu, M (MARCEL DEKKER INC, 1997)
The removal of cobalt (II) ion from aqueous solutions, by adsorption on activated carbon prepared from the rice hulls (ACRH), has been investigated depending on pH, activated carbon dosage, contact time, initial metal concentration and solution temperature. The optimum values of pH, ACRH dosage and contact time have been determined as 6-7, 1.5 g ACRH/50 mt solution and 40 minutes respectively. Freundlich and Langmuir isotherm constants have been calculated at two different temperatures of 293 K and 313 K. Furthermore the other thermodynamic data for Delta G degrees and Delta S degrees, have been also calculated at two temperatures of 293 K and 313 K. The adsorption of Co (II) ion from aqueous solutions has been found to be exothermic (Delta H degrees=-1.543 KJ/mol).
Keywords: adsorption; cobalt; activated carbon; rice hulls; FLY-ASH; REMOVAL; Engineering; Environmental Sciences & Ecology